The issues of churches and temples in the modern era - Mohammed Sabbar Taha,; Abdull Rahman Mahmood,; Jaffary Awang, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Rasulullah SAW as a final prophet is a great rewards of Allah SWT to Muslims ummah. The Allah's syariah is the best method for all human beings in religious affairs and worldly affairs until the day of judgement. This syariah has abolished all the previous syariah. However, the syariah still protects the rights and the responsibility of other religions who are living in the Islamic State by giving the rights of social freedom, business activities and the right to practice their rituals beliefs. All these issues are being allowed under the system of ahl zimmah concept where their rights must be protected. However, the current developments have shown the tension in Muslim countries regarding the development of temple and church. Therefore, the purpose of this study is to discuss the perspective of the Islamic aqidah on building the temple and church and the misunderstanding on the issues of building the temple and church in the Islamic state. This study uses the data collection method and analyzing the Islamic scholars' views by identifying the authentic view on this issue and how far its relevance with the current development. The findings have shown that the temple and the church are prohibited to be built in certain areas in the Islamic countries and being allowed to be built in other areas according to difference country. It depends on the agreement between Islamic leaders and ahl zimmah as long as it will brings the harmonious between religion and Islamic community.